BOUNDLESS CREATION, VIRTUAL MUSIC AND GLOBAL COLLABORATION - Justin, Rizky Stephanie; Darmayuda, I Komang (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
The advent of digital technologies has revolutionized the way music is created, shared, and experienced, thereby enabling a new era of boundless creation through virtual music. This study explores how the convergence of digital tools, virtual platforms, and global connectivity has transformed the landscape of music production, fostering unprecedented opportunities for collaboration across borders, cultures, and genres. Musicians, producers, and composers can now create, record, and perform together in virtual spaces regardless of their physical location. By leveraging cloud-based software, real-time collaboration tools, and virtual instruments, creators are no longer limited by geographical constraints, allowing for more diverse, innovative, and experimental work. The study also examines the impact of virtual music on the global music industry, including its role in democratizing access to music production, expanding audience reach, and reshaping traditional models of distribution and performance. Ultimately, the fusion of virtual music and global collaboration has opened new avenues for artistic expression, cross- cultural exchange, and creative freedom.